2018
DOI: 10.1200/po.18.00163
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Gene Expression Classifiers in Men With Newly Diagnosed Prostate Cancer

Abstract: Purpose Tissue-based gene expression classifiers (GECs) may assist with management decisions in patients with newly diagnosed prostate cancer. We sought to assess the current use of GEC tests and determine how the test results are associated with primary disease management. Methods In this observational study, patients diagnosed with localized prostate cancer were tracked through the Michigan Urological Surgery Improvement Collaborative registry. The utilization and results of three GECs (Decipher Prostate Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…[131][132][133][134][135][136][137][138][139][140] A prospective, clinical utility study of 3,966 patients newly diagnosed with localized prostate cancer found that the rates of active surveillance increased with use of a tissue-based gene expression classifier. 141 Active surveillance rates were 46.2%, 75.9%, and 57.9% for those whose classifier results were above the specified threshold, below the threshold, and those who did not undergo genomic testing, respectively (P,.001). The authors estimate that 1 additional patient may chose active surveillance for every 9 men with favorable risk prostate cancer who undergo genomic testing.…”
Section: Tumor Multigene Molecular Testingmentioning
confidence: 97%
“…[131][132][133][134][135][136][137][138][139][140] A prospective, clinical utility study of 3,966 patients newly diagnosed with localized prostate cancer found that the rates of active surveillance increased with use of a tissue-based gene expression classifier. 141 Active surveillance rates were 46.2%, 75.9%, and 57.9% for those whose classifier results were above the specified threshold, below the threshold, and those who did not undergo genomic testing, respectively (P,.001). The authors estimate that 1 additional patient may chose active surveillance for every 9 men with favorable risk prostate cancer who undergo genomic testing.…”
Section: Tumor Multigene Molecular Testingmentioning
confidence: 97%
“…Traditionally, Gleason score, clinical staging and PSA at diagnosis have helped classifying localized PCs as being at low, intermediate, and high risk of relapse [ 88 ]. Recently several tissue-based multigene expression (Decipher, Oncotype Dx Prostate, Polaris) and a protein-based (ProMark) classifiers have been proposed to identify patients with biologically significant disease [ 89 , 90 , 91 , 92 ].…”
Section: Use Of Molecular Biomarkers In Localized Prostate Cancermentioning
confidence: 99%
“…), these classifiers (Decipher, Oncotype Dx Prostate, Polaris) offer scores that, integrating other clinical–pathological features, might help identifying patients with localized disease but with worse outcomes. Potentially, these tools could help clinicians in deciding which patients would benefit from surveillance vs. active treatment, or a salvage approach after a radical treatment [ 89 , 90 , 91 , 92 ].…”
Section: Use Of Molecular Biomarkers In Localized Prostate Cancermentioning
confidence: 99%
“…However, there is no high-quality comparative data to determine which of the markers is the most accurate prognosticator. Longer term data is needed to determine whether their utility will impact patient quality of life and prostate cancer specific outcomes [22,29,30]. They may be useful when combined with known risk stratification systems in prostate cancer.…”
Section: Molecular Biomarkers and Gene Alterations In Prostate Cancermentioning
confidence: 99%